THE SACRED FACE OF INDIGENOUS BELIEF: A CRITICAL REVIEW ON THE MYTHOLOGY OF NYAI RORO KIDUL THROUGH MARY FAT FISHER AND ROBIN RINEHART'S THEORY OF INDIGENOUS SACRED WAYS - Nurrachman, Dian; Truna, Dody S.; Hannah, Neng (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2024)
In many myths and legends, Nyai Roro Kidul is believed to be a semi-divine being or a beautiful princess with mystical qualities. Known as the Queen of the Southern Sea (Indian Ocean), she embodies a unique fusion of local spiritual beliefs, Hindu-Buddhist influences, and, later, Islamic cultural integration. Her narrative not only reflects the Javanese people’s interaction with nature and the supernatural world but also encapsulates deeper meanings related to power, gender, and the relationship between humans and the divine. Those who seek wealth often glorify Nyai Roro Kidul, even if it means promising the souls of family members as an offering. The story of Nyai Roro Kidul, believed by many traditional Javanese, remains controversial today. Some believe in her and even claim to have encountered her, while many others consider it just folklore. In reality, belief in Nyai Roro Kidul is not confined to indigenous communities but also extends to modern intellectuals, especially Javanese mystics. Fisher and Rinehart discuss important aspects of cultural diversity leading to syncretism in detail, such as the reliance on oral traditions among the people. Likewise, the mythology of Nyai Roro Kidul has been passed down orally through various stories, making her narrative widespread and a common feature of the belief systems among communities along Java’s southern coast as part of a "living religion" from the perspective of indigenous sacred ways.